Postural and respiratory function of the abdominal muscles: A pilot study to measure abdominal wall activity using belt sensors - Novak, Jakub; Busch, Andrew; Kolar, Pavel; Kobesova, Alena (Isokinetics and exercise science, 2021)
BACKGROUND: The abdominal muscles play an important respiratory and stabilization role, and in coordination with other muscles regulate intra-abdominal pressure (IAP) to stabilize the spine. OBJECTIVE: To examine a new, non-invasive method to measure activation of the abdominal wall and compare changes in muscle activation during respiration while breathing under a load, and during instructed breathing. METHODS: Thirty-five healthy individuals completed this observational crossover study. Two capacitive force sensors registered the abdominal wall force during resting breathing stereotype, instructed breathing stereotype and under a load. RESULTS: Mean abdominal wall force increased significantly on both sensors when holding the load compared to resting breathing (Upper Sensor: P < 0.0005, d = - 0.46, Lower Sensor: P < 0.0005, d = - 0.56). The pressure on both sensors also significantly increased during instructed breathing compared to resting breathing (US: P < 0.0005, d = - 0.76, LS: P < 0.0005, d = - 0.78). CONCLUSIONS: The use of capacitive force-sensors represent a new, non-invasive method to measure abdominal wall activity. Clinically, belts with capacitive force sensors can be used as a feedback tool to train abdominal wall activation.